2006
DOI: 10.1007/s10585-006-9006-1
|View full text |Cite
|
Sign up to set email alerts
|

RANKL-induced CCL22/macrophage-derived chemokine produced from osteoclasts potentially promotes the bone metastasis of lung cancer expressing its receptor CCR4

Abstract: Chemokines are now known to play an important role in cancer growth and metastasis. Here we report that differentiating osteoclasts constitutively produce CCL22 (also called macrophage-derived chemokine) and potentially promote bone metastasis of lung cancer expressing its receptor CCR4. We first examined expression of chemokines by differentiating osteoclasts. CCL22 was selectively upregulated in osteoclast-like cells derived from RAW264.7 cells and mouse bone marrow cells upon stimulation with RANKL (recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 27 publications
2
67
0
4
Order By: Relevance
“…Stimulation of osteoclastlike cells with CCR4 results in up-regulation of its ligand, CCL22. In addition, it has been demonstrated that a human lung cancer cell line, which expresses CCR4 metastasizes to bone when injected intravenously into NK cell-depleted SCID mice [136]. Together, the above data supports that the expression of chemokine ligands or their receptors in the organ environment or by malignant cells plays a major role in organ-specific metastasis.…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 60%
See 1 more Smart Citation
“…Stimulation of osteoclastlike cells with CCR4 results in up-regulation of its ligand, CCL22. In addition, it has been demonstrated that a human lung cancer cell line, which expresses CCR4 metastasizes to bone when injected intravenously into NK cell-depleted SCID mice [136]. Together, the above data supports that the expression of chemokine ligands or their receptors in the organ environment or by malignant cells plays a major role in organ-specific metastasis.…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 60%
“…It was demonstrated that CCR7 and CXCR4 that are highly expressed in breast cancer cells determine the invasion and organ specificity of breast cancer metastasis [133] The ligands CCL21 and CXCL12 for these receptors exhibit higher expression in the organs (lung and liver) that are preferred sites for breast cancer metastasis [133]. Recently, it has been suggested that osteoclasts may promote metastasis of lung cancer cells expressing CCR4 to the bone marrow by producing its ligand CCL22 [136]. Stimulation of osteoclastlike cells with CCR4 results in up-regulation of its ligand, CCL22.…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%
“…SDF-1 gradients mediate HSC retention within BM niches, and growing evidence suggests that CXCR4-expressing cancer cells home to bone in a similar fashion, where they may lodge in the pre-existing supportive stromal microenvironment (Muller et al 2001;Kaifi et al 2005). Bone expresses particularly high levels of SDF-1, and osteotropic cancers such as breast, ovarian, prostate, and neuroblastoma metastasize to bones in a CXCR4-dependent manner (Ge- Furthermore, neutralization of the SDF-1/CXCR4 axis can block prostate metastasis and growth in osseous sites (Nakamura et al 2006). Differentiating osteoclasts constitutively produce chemokine CCL22 and may promote bone metastasis of lung cancer cells expressing its receptor CCR4 (Nakamura et al 2006).…”
Section: Changes In the Bm Microenvironmentmentioning
confidence: 99%
“…Chemokines and their corresponding receptors have established roles in directing cell migration in many different types of cancer; and expression levels of these proteins have also correlated with clinical outcomes [24][25][26][27][28][29]. The role of CCL25-CCR9 signaling in modulating metastasis was initially reported by Letsch There is an absence of CCL25 staining within the normal architecture of the pancreatic duct and stroma c. In the malignant pancreatic lesion, with characteristic nuclear crowding, enlarged nuclei, and rare mitoses, there is moderate heterogeneous immunostaining for CCL25 protein in the nuclei.…”
Section: Discussionmentioning
confidence: 99%